Fatty acid composition of sheep milk from a backcross Sarda x Lacaune resource population: Preliminary QTL detection for CLA content - Carta A.; Piredda G.; Addis M.; Cabiddu A.; Fiori M.; Leroux C.; Barillet F. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
Fatty acid composition of milk fat of 847 Sarda ï Lacaune backcross ewes was determined. Main attention was given to fatty acids that could play a positive role on human health (butyric, oleic, C18 to C22 polyunsaturated acids and conjugated linoleic acid (CLA)). A preliminary phenotypic analysis was carried out for QTL detection on the whole genome, mainly focusing on CLA, to study the expression level of some enzymes involved in the mammary bio-synthesis of fatty acids. A preliminary QTL analysis on the OAR 22, where the SCD gene encoding delta 9-desaturase is located, allowed a putative QTL to be detected for the CLA:vaccenic acid ratio segregating in families 1 and 4. An SCD candidate gene approach will be implemented by quantification of the mRNA of the SCD gene in the milk of around 100 ewes chosen in the high and low tails for the CLA:vaccenic acid ratio of families 1 and 4.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)